The Eastern Churches and the Reformation in the Sixteenth and Seventeenth Centuries - Cooper, David J. C. (Scottish journal of theology, 1978)
The purpose of this paper will be to examine the encounters between Eastern Christendom and the Western Reformation of the Church. The study will include an analysis of the historical background, an introduction to the chief characters involved, and an evaluation of doctrinal issues that have represented the divergent paths of Orthodoxy and Protestantism.